The Effect of Emotional Intelligence Training on Academic Commitment, Emotional Self-Regulation, and Academic Performance of Male Students at Farhangian University in Khuzestan Province - Salehi Shablizi , Masoud; Haji Yakhchali, Alireza; Shehni Yailagh , Manijeh; Maktabi , Gholamhossein (Health Nexus, 2025)
This study aimed to examine the effect of emotional intelligence training on academic commitment, emotional self-regulation, and academic performance in male students at Farhangian University in Khuzestan. The study utilized an experimental field design with a pretest-posttest control group structure. The statistical population included all male students at Farhangian University in Ahvaz during the 2017–2018 academic year. A total of 72 students were randomly selected and assigned to either the experimental group (n = 36) or the control group (n = 36). The intervention consisted of ten one-hour sessions of emotional intelligence training based on Bar-On’s model. The data collection instruments included the Academic Commitment Scale (Fredricks et al., 2004), the Emotional Self-Regulation Scale (Gross & John, 2003), and academic performance measured by students’ semester grade point averages. Data analysis was conducted using multivariate analysis of covariance (MANCOVA) and analysis of covariance (ANCOVA) to determine the effectiveness of the intervention. The results showed that emotional intelligence training had a significant positive effect on academic commitment (F(1, 64) = 7.14, p = 0.009), emotional self-regulation (F(1, 64) = 8.21, p = 0.006), and academic performance (F(1, 64) = 9.48, p = 0.004). The experimental group demonstrated higher scores in all three variables compared to the control group. The intervention was particularly effective in enhancing students’ ability to regulate emotions and remain committed to their academic responsibilities. The findings suggest that emotional intelligence training can improve students’ academic commitment, enhance their emotional self-regulation, and lead to better academic performance. Implementing emotional intelligence training in teacher education programs at Farhangian University may foster long-term improvements in both students’ personal development and their future impact as educators